Loss-cone-shift maps for the Earth’s magnetosphere - Borovsky, Joseph E. (Frontiers in Astronomy and Space Sciences, 2022)
Because of finite-gyroradii effects, the atmospheric loss cone for energetic particles in the magnetosphere is shifted away from the magnetic-field direction. Using the Tsyganenko T96 magnetic-field model, maps of the magnitude of the angular shift of the loss cone are created for electrons, protons, and singly-ionized oxygen in the nightside magnetosphere. When the shift exceeds about 5o - 10o, stochastic scattering of particles occurs. For protons and oxygen, this loss-cone shift is quite large, even in the dipolar portions of the magnetosphere, and stochastic scattering of protons and oxygen can occur in those regions. Hence, the ring-current ion population probably exhibits a robustly shifted loss cone and stochastic scattering in the dipole magnetosphere. For electrons, large loss-cone shifts and stochastic scattering are restricted to the magnetotail near and beyond the transition region.